Análise ex ante de políticas públicas: Fundamentos teórico-conceituais e orientaç\~oes metodológicas para a sua aplicaç\~ao prática - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– When governments launch policies or programs without any prior analysis, with unclear objectives, undefined or unjustifiable public selection, poorly conceptualized interventions, fragmented and often contradictory actions, without indicators and targets, and with insufficient inputs (small and poorly trained teams; reduced budget, and intermittent flow of resources), the chance that anything goes right is zero. The ex-ante analysis is an examination that seeks to identify inconsistencies and incoherences and fill in some of these gaps with answers and recommendations. This true existential void of many policies and programs that always had or have acquired difficulties in answering who are we, where do we come from and where are we going to makes ex-ante analysis more necessary than ever. The ex-ante analysis is an approach with a very specific methodology and is still mastered by a few people. The main purpose of this working paper is to detail and clarify the references and, more precisely, the ex-ante analysis methodology, in order to make it increasingly user-friendly, practical, applied, and in the public domain. The paper provides a roadmap to leaders, policymakers, program designers, public managers, advisors, consultants, and the public. If they gain fluency in ex-ante's grammar, they will be more assertive in the dialogue for solutions to overcome collective problems. This working paper also encourages the formation of a community of experts in moderation and process facilitation of ex-ante analysis. Such qualification is crucial for crafting policies and programs born ready to be monitored and evaluated so as to demonstrate their "raison d'être" to the public.
10419/284873
Keywords: D04; H11; H43; 330; ex-ante analysis of public policies; formulation; implementation; monitoring; evaluation; microeconomic public policy